Diachronic Change in the Meaning of Timē: From Homer to Isocrates - Ρηγάλος, Δημήτριος (Πανεπιστήμιο Πελοποννήσου, 2023)
The study aimed to examine how the concept of Timē changed from the Geometric Period to the Classical Period and how it affected the social strata within the society, through the works of Homer and Isocrates for those two periods. Social coexistence is a complex situation that affects, and it is affected by actions and interactions, and where individuals have different social roles and social positions. Timē, a term parallel to respect and honour, in its cultural framework during Ancient Greece placed importance on developing and sustaining reputation to fundamental cultural traits, particularly retribution to reputation threats. Adding to this, ethos presented the character of individuals, and it was closely related to Timē. In Geometric Period and in Classical Period, Timē was a regulating factor for social coexistence. For the fulfillment of the aim of the study, a Qualitative Research approach was used, with analytical and critical element, while for literature review primary and secondary sources were used. From the analysis in the Texts of Homer and Isocrates, derives a structural depiction of Timē, based on interpersonal interaction, using a vertical and horizontal system of Timē and personal assessment using ethos and the social perception of the individual. In the system, Vertical honour is present when interacting with someone by rank, family, achievements, social status, and divine provenance. In the system, Horizontal honour is present when interacting with someone with an equal ranking, social position, and social role. Ethos is the equivalent of the moral intentions and the actions through προαίρεσιν, while social perception has to do with one’s social value, reputation, and prestigious recognition, from the eyes of the individual. From the text of the Homer, in the Geometric period, it is clear that someone won or competed for Timē, in activities related to war, duels, gifts, war spoils, competitions, and interaction with someone from a higher position in the vertical honour system. From the texts of Isocrates, in the classical period, it is clear that someone won or competed for Timē, in activities related to war, public office, social position, competitions, wealth, and offerings to the city.
Keywords: Χρόνος - Φιλοσοφία; Φιλοσοφία της φύσης; Ανθρώπινα δικαιώματα; Κοινωνική αντίληψη; Social perception; Όμηρος; Ισοκράτης; Time - Philosophy; Philosophy of nature; Human rights; Social perception; Homer; Isocrates; Timē; Ethos; Honour; Honor; Isocrates; Homer; Geometric Period; Classical Period